2016
DOI: 10.1016/j.rgmx.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Dispepsia funcional y dispepsia asociada a infección por Helicobacter pylori: ¿son entidades con características clínicas diferentes?

Abstract: The patients with dyspepsia infected with Helicobacter pylori had similar clinical characteristics to the non-infected patients and could not be differentiated a priori. The prevalence of Helicobacter pylori infection in patients with functional dyspepsia was 58% and increased with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Their study resulted in finding a high prevalence of patients with dyspepsia and H. pylori infection [21]. In another cross-sectional study, Rodríguez-García et al enrolled 578 patients with dyspepsia with no endoscopic lesions and divided them into two groups according to having (n=336) or not having H. pylori infection (n=242) [22]. Then, they were compared according to clinical characteristics, medical history, comorbidities, and usage of health resources.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study resulted in finding a high prevalence of patients with dyspepsia and H. pylori infection [21]. In another cross-sectional study, Rodríguez-García et al enrolled 578 patients with dyspepsia with no endoscopic lesions and divided them into two groups according to having (n=336) or not having H. pylori infection (n=242) [22]. Then, they were compared according to clinical characteristics, medical history, comorbidities, and usage of health resources.…”
Section: Reviewmentioning
confidence: 99%
“…Then, they were compared according to clinical characteristics, medical history, comorbidities, and usage of health resources. They found 58% of cases with dyspeptic symptoms have H. pylori infection without detectable endoscopic lesions [22].…”
Section: Reviewmentioning
confidence: 99%
“…A general invitation was made to patients with gastric symptoms from daily clinical practice. Patients, men, and women 18 years or older who volunteered to participate were evaluated by anamnesis and survey for general data and the presence or absence of clinical symptoms (upper abdominal pain, heartburn with or without reflux, nausea or vomiting, loss of appetite, or early fullness) associated with functional dyspepsia (Rodríguez‐García and Carmona‐Sánchez 2016 ). Periodontal examination and classification were performed according to the tables by Tonetti, Greenwell, and Kornman ( 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Dyspeptic patients infected with H. pylori have similar clinical characteristics to non-infected dyspeptic patients. 95 A previous study showed that epigastric pain or burning and postprandial fullness are more intense in dyspeptic patients infected with H. pylori than in non-infected dyspeptic patients. 96 …”
Section: Association Of Helicobacter Pylori Infection With Symptom-based Subtypes Of Functional Dyspepsiamentioning
confidence: 98%